The Effect of COVID-19 on Cardiovascular Diseases and the Need for Beta-Blocker Dose Modification - Jędrasek, Tomasz; Jędrasek, Aleksandra; Gawryś, Jakub (Journal of Education, Health and Sport, 2024)
Introduction and purpose: The Coronavirus Disease 2019 (COVID-19) and its effects on patients remain the main focus of many researchers across the world. One of the challenges faced by medical professionals is the impact of the infection on the course of chronic diseases. Manifestations of the infection are observed mainly in the respiratory system, but other organs, particularly the cardiovascular system, are also frequently affected. Recent data indicates that arterial hypertension and cardiovascular diseases (CVD) are the most prevalent comorbidities in patients suffering from SARS-CoV-2 infection. Material and methods: This study aimed to investigate the impact of SARS-CoV-2 infection on the cardiovascular system. Apart from the literature review we conducted a retrospective study to check the necessity for modification of chronic treatment in patients with CVD after recovery from COVID-19, particularly regarding the use of beta blockers. Results: Using the Mann-Whitney U test a positive correlation (p = 0.04) was found between the presence of coronary artery disease before COVID-19 and a need for an increase in the beta-blockers dose. Conclusions: Patients with preexisting CVD should be closely monitored during and after recovery from SARS-CoV-2 infection due to the higher risk of complications and the potential need for modifications in the treatment of chronic diseases. Patients with coronary artery diseases may need an increase in beta-blocker doses after recovery. This is an important issue for future research, especially in the context of long COVID-19.